1998
DOI: 10.1111/j.1751-1097.1998.tb05297.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Fluorescence Quenching of Blepharisma japonicum Photoreceptor Pigments

Abstract: Abstract— The hypericin analogs blepharismin (BP), oxyblepharismin (OxyBP) and stentorin (ST), the photosensing chromophores responsible for photomotile reactions in the ciliates Blepharisma japonicum (red and blue cells) and Stentor coeruleus, represent a new class of photoreceptor pigments whose chemical structures have recently been determined. In the case of ST it has been shown that the first excited singlet state can be deactivated by donation of an electron to an appropriate acceptor molecule (e.g. a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
4
23
1
Order By: Relevance
“…On the other hand, semiempirical molecular orbital calculations confirmed that the highest occupied molecular orbital (HOMO) of an azobenzene group is located at higher energy by 2-3 eV compared with the laser dyes. Thus, it is suggested that the photoexcitation of a dye molecule induced absorption saturation of pDR1M through oxidative electron transfer from azobenzene to the dye [3,4] in ca. 3 ps.…”
Section: Fluorescence Dynamics Of Organic Laser Dyes In Azobenzene Pomentioning
confidence: 99%
“…On the other hand, semiempirical molecular orbital calculations confirmed that the highest occupied molecular orbital (HOMO) of an azobenzene group is located at higher energy by 2-3 eV compared with the laser dyes. Thus, it is suggested that the photoexcitation of a dye molecule induced absorption saturation of pDR1M through oxidative electron transfer from azobenzene to the dye [3,4] in ca. 3 ps.…”
Section: Fluorescence Dynamics Of Organic Laser Dyes In Azobenzene Pomentioning
confidence: 99%
“…The type of fluorescence quenching can be determined by bimolecular quenching constant ( K q ). When the fluorescent lifetime (τ 0 ) and K SV are known, bimolecular quenching constant is calculated by the following equation : Knormalqτ0=K SV …”
Section: Resultsmentioning
confidence: 99%
“…The type of fluorescence quenching can be determined by bimolecular quenching constant (K q ). When the fluorescent lifetime (τ 0 ) and K SV are known, bimolecular quenching constant is calculated by the following equation [34]: The fluorescence lifetime of TGA-CdTe QDs was typically in the range of 6-11 ns with the change of particle size. Therefore, K q was at 10 12 order of magnitude by formula of calculation K q =K SV /τ 0 , which far outweighed the maximum dynamic fluorescence collision quenching constant of (1.0-2.0) × 10 10 L/mol/s [35].…”
Section: Discussion On the Mechanism Of Fluorescence Quenchingmentioning
confidence: 99%
“…Previous study (15) has demonstrated that purified free cise, some of the light-excited OxyBL are able to decay through the deexcitation pathway other than radiative transition, such as an electron transfer, (17) which is possibly responsible for the photosignal transduction leading to the modification of photobehavior in Blepharisma. The pigments eluted in fraction I are not associated with the proteins, or are not specifically associated with the proteins if they are bound.…”
Section: Resultsmentioning
confidence: 99%